Pasang Surut Hubungan Aceh dan Turki Usmani: Perspektif Sejarah - Burhanudin, Jajat (Studia Islamika, 2016)
A. C. S. Peacock and Annabel Teh Gallop, eds. 2015. From Anatolia to Aceh: Ottomans, Turks, and Southeast Asia. Oxford: The British Academy by Oxford University Press.This book comprises of some articles with the major contribution to investigating further the relation between the Ottoman in Istanbul and Muslim kingdoms in Southeast Asia. Using the archival sources from the Ottoman period, those articles highlight new information on the Ottoman-Southeast Asia network, which has been rather neglected from any scholarly studies. Especially in relation with the Acehnese kingdom, the discussions of this book demonstrate that Aceh was the only Southeast Asian Islamic kingdom which made serious efforts to make relation with the Ottoman. Issues related to politics, commerce, and military aids constituted the main substance in the relation they established in the sixteenth century, which then continued in the seventeenth century in the form of intellectual and religious network. The period of the nineteenth century witnessed the re-emergence of the political issue in Aceh-Ottoman relation, as Aceh looked for Ottoman protection to face the Dutch military invasion.DOI:Â 10.15408/sdi.v23i2.3259